Semantic web: Data representation in a distributed environment / Azhar Tajul Noor - Azhar Tajul , Noor (2008)
This thesis discusses the development of specific tools such as XML–SOAP-based system towards the realization of the Semantic Web. Semantic Web can be seen as a huge engineering solution, once it becomes easier to publish data in a repurposable form. In this thesis, the Semantic Web discussion is generally involved on syntaxes which use to represent data. As implementing the Semantic Web requires adding semantic metadata to the information resources, XML-SOAP-based system has paved the road by adding some metadata in the form of human-readable tags that describe data. In addition, XML documents can include information about the author of a web page, relevant keywords for search engine optimization, and the software tools used to create the XML file. This will allow machines to effectively process the data based on the semantic information that describes it.